Nature of Intense Magnetism and Differential Rotation in Convective Dynamos of M-dwarf Stars with Tachoclines - Connor P. Bice; Juri Toomre (The Astrophysical Journal, 2023)
Many of the M-dwarf stars, though they are tiny and dim, are observed to possess strong surface magnetic fields and exhibit remarkably intense flaring. Such magnetism may severely impact habitability on the exoplanets now discovered nearby. The origin of the magnetism must rest with dynamo action achieved by turbulent convection coupled to rotation within the M-dwarfs. To further explore the nature and diversity of the magnetism that can result, we turn here to an extensive set of 45 global MHD simulations to explore dynamos operating within deep convective envelopes of rapidly rotating M2 (0.4 M _⊙ ) stars. We observe a wide range of cycle periods present in the convection zones, whose durations we find to scale with the Rossby number as Ro ^−1.66±0.07 in concurrence with scalings identified in simulations of more massive stars. We find a unifying relationship between the ratio of magnetic to convective kinetic energy (ME/CKE) and the degree to which the differential rotation is quenched by magnetic fields. We show that the presence of a tachocline in these model stars enhances their axisymmetric magnetic field components, leading to a surface dipole fraction on average 78% greater than an equivalent star with only a CZ, potentially shedding light on the nature of the tachocline divide through resultant effects on the spin-down rate.